Development and application of a multi-axis dynamometer for measuring grip force - Irwin, C. B.; Towles, J. D.; Radwin, R. G. (Ergonomics, 2013)
Objective: This paper describes the development and application of a novel multi-axis hand dynamometer for quantifying 2D grip force magnitude and direction in the flexion-extension plane of the fingers. Methods: A three-beam reconfigurable form dynamometer, containing two active beams for measuring orthogonal forces and moments regardless of point of force application, was designed, fabricated and tested. Maximum grip exertions were evaluated for 16 subjects gripping cylindrical handles varying in diameter. Results: Mean grip force magnitudes were 231 N (SD = 67.7 N), 236 N (72.9 N), 208 N (72.5 N) and 158 N (45.7 N) for 3.81 cm, 5.08 cm, 6.35 cm and 7.62 cm diameter handles, respectively. Grip force direction rotated clockwise and the centre of pressure moved upward along the handle as handle diameter increased. Conclusions: Given that the multi-axis dynamometer simultaneously measures planar grip force magnitude and direction, and centre of pressure along the handle, this novel sensor design provides more grip force characteristics than current sensor designs that would improve evaluation of grip characteristics and model-driven calculations of musculoskeletal forces from dynamometer data.